Isolated Regan-Morrey type III fracture of the ulnar coronoid process: a report of two cases - Kow, Ren Yi; Mustapha@Zakaria, Zaharul Azri; Mor Japar Khan, Ed Simor Khan; Low, Chooi Leng (Indian Orthopaedic Research Group, 2018)
Introduction:Fracture of the ulnar coronoid process is uncommon. It is commonly associated with posterior dislocation of the elbow, but it may also present as an isolated fracture. In general, all ulnar coronoid process fractures with elbow joint instability and large fracture fragments are fixed surgically. We report two cases of the rare isolated Regan-Morrey type III ulnar coronoid process fractures and their outcomes. Case Report:Case Report 1: Mrs P, a 27-year-old right-hand dominant female, was involved in a motor vehicle accident (MVA) and sustained an isolated Regan-Morrey type III ulnar coronoid process fracture. In view of the large coronoid process fragment causing elbow joint instability, she underwent an open reduction and internal fixation when the elbow swelling had subsided. An anterior approach was used to identify the fracture fragment and it was fixed with two half-threaded cancellous lag screws with washers to achieve an anatomical reduction. Postoperatively, she recovered with excellent outcome based on the Mayo elbow performance score (MEPS). Case Report 2: Mr M, a 23-year-old right-hand dominant gentleman, was involved in a MVA and sustained an isolated Regan-Morrey type III ulnar coronoid process fracture. During examination under general anesthesia, passive range of the movement of his right elbow was noted to be <90°due to the impaction of the fracture fragment. An open reduction through an anterior approach was performed and Kirschner wires were inserted to fix the coronoid process fracture. Kirschner wires were opted for the ease of post-operative removal as the patient was not keen to have a retained implant after recovery. He recovered with good outcome based on the MEPS. Conclusion: Isolated fracture of the ulnar coronoid process is rare. Open reduction and internal fixation is mandatory for patients with coronoid process fracture and unstable elbow joint to achieve good functional outcomes.